2020
DOI: 10.1089/ast.2019.2106
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Detection of Biosignatures at Lake Tírez, Spain: Implications for Mars

Abstract: The detection of potential biosignatures with mineral matrices is part of a multifaceted approach in the search for life on other planetary bodies. The 2020 ExoMars Rosalind Franklin rover includes within its payload three IR spectrometers in the form of ISEM (Infrared Spectrometer for ExoMars), MicrOmega, and Ma-MISS (Mars Multispectral Imager for Subsurface Studies). The use of this technique in the detection and characterization of biosignatures is of great value. Organic materials are often co-deposited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Regarding the archaeal domain, the few references available (Refs. 16 , 22 ; this work) confirm that the members of the Halobacteriaceae family are well adapted to both the humid and dry ecosystems of Tirez, being predominant in both conditions. Preston et al 22 found that the second most abundant group of archaea in the dry sediments of Tirez was the Methermicoccaceae family, within the Methanosarcinales order, Methanomicrobia class.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Regarding the archaeal domain, the few references available (Refs. 16 , 22 ; this work) confirm that the members of the Halobacteriaceae family are well adapted to both the humid and dry ecosystems of Tirez, being predominant in both conditions. Preston et al 22 found that the second most abundant group of archaea in the dry sediments of Tirez was the Methermicoccaceae family, within the Methanosarcinales order, Methanomicrobia class.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, the lipid biomarkers analysis was able to detect compounds specific of additional microbial sources, such as cyanobacteria 36 ( n -C 17 , C 17:1 , or 7Me-C 15 and 7Me-C 17 ), microalgae and/or diatoms (phytosterols 37 ; or C 20:5 , and C 22:6 alkanoic acids 30 ), and other photoautotrophs (phytol and potentially degradative compounds such as pristane and phytane 31 ). A relatively higher preservation of the cell-membrane remnants (i.e., lipids) compared to the DNA-composing nucleic acids may contribute to explain the lack of detection of cyanobacteria, diatoms and microalgae, and other phototrophs by DNA analysis (a deficit in our results shared with Montoya et al 16 , and Preston et al 22 ). Although abundant in higher plants 38 , sterols such as those detected here (i.e., the sterols campesterol, stigmasterol, and β-sitosterol, as well as ergosterol) are also major sterols in some microalgal classes 37 (such as Bacillariophyceae, Chrysophyceae, Euglenophyceae, Eustigmatophyceae, Raphidophyceae, Xanthophyceae, and Chlorophyceae), cyanobacteria (β-sitosterol), and fungi (ergosterol 39 ).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Investigation on the stability or degradation-rate of any biomarker after exposure to simulated or real space conditions is of high interest for space exploration. The stability of any biomarker is dependent on its initial form, the matrix in which it is hosted, and the chemical and physical processes to which it is subjected over time [19].…”
Section: Discussionmentioning
confidence: 99%
“…Organic, metabolic and morphological structure or compounds of the organisms could persist in mineral structures and are considered good biomarkers of microorganisms' presence. On Earth, biological matter can be preserved in sedimentary rocks as carbonaceous macromolecules [12] and maybe, if life exists or existed on Mars, its rocks could preserve organic deposits: organic components may be preserved either as degraded molecules within mineral structures or as disseminated molecules chemically bonded to mineral particles of rocks, such as phyllosilicates [19].…”
Section: Introductionmentioning
confidence: 99%